2002
DOI: 10.1001/archotol.128.9.1013
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With CHARGE Association

Abstract: Variations in the temporal bone anatomy of patients with CHARGE association can lead to increased technical challenges and risk to the facial nerve during cochlear implantation. Individual outcomes after implantation may vary; our patients receiving implants obtained benefit. Parents should be counseled thoroughly and have appropriate expectations before proceeding with implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 9 publications
2
30
0
3
Order By: Relevance
“…28,29 Facial and auditory nerve miswiring has also been reported in CHARGE syndrome and was found in one participant (Case 5) in our study. 30 Congenital aberrant innervation may support a primary neural pathology underlying the vertical deviations noted in our study participants.…”
Section: Volume 12 Number 5 / October 2008 Mcmain Et Almentioning
confidence: 78%
See 1 more Smart Citation
“…28,29 Facial and auditory nerve miswiring has also been reported in CHARGE syndrome and was found in one participant (Case 5) in our study. 30 Congenital aberrant innervation may support a primary neural pathology underlying the vertical deviations noted in our study participants.…”
Section: Volume 12 Number 5 / October 2008 Mcmain Et Almentioning
confidence: 78%
“…Deafness in CHARGE syndrome is speculated to arise from congenital defects of the ossicular chain, "dysplasia" of the bony labyrinth, eustantian tube dysfunction, and high frequency sensorineural loss. 21,26,30 Clinical neurological testing was conducted because detailed cranial magnetic resonance imaging was unavailable. Recent magnetic resonance imaging data from Europe revealed anomalies of olfactory tracts and bulbs in 100% of CHARGE syndrome patients, varying from moderate hypoplasia to complete aplasia.…”
Section: Volume 12 Number 5 / October 2008 Mcmain Et Almentioning
confidence: 99%
“…This is because aplasia or hypoplasia of the semicircular canals is present in 95% of individuals with a pathogenic variant in the CHD7 gene, making it one of its most prevalent clinical features (Abadie et al, 2000; Bauer, Goldin, & Lusk, 2002; Lemmerling et al, 1998; Morimoto et al, 2006; Tellier et al, 1998; Wiener‐Vacher, Amanou, Denise, Narcy, & Manach, 1999). The configuration of the labyrinth in CHARGE syndrome is typical: a malformed vestibule and aplastic or hypoplastic semicircular canals that is sometimes combined with cochlear malformation.…”
Section: Diagnostic Value Of Cranial Imagingmentioning
confidence: 99%
“…Usher syndrome is one of the 20% of causes of deafness that involve abnormalities in cochlea-vestibular anatomy. These abnormalities increase the potential for surgical difficulties and complications, such as damage to the facial nerve and incomplete insertion of the implant electrode array in the cochlea (Bauer et al, 2002;Chadha et al, 2009).…”
Section: Candidacy and Selected Aetiologies/pathologies Of Deafnessmentioning
confidence: 99%
“…Despite these difficulties, initial results for small numbers of children with cochlear anomalies have shown that implantation is possible, with some children achieving speech perception and language results similar to those without anatomical abnormalities (Chadha et al, 2009;Dettman et al, 2011). Children with a common cavity anomaly (a single cavity in the cochlea) and other more severe syndromic anomalies have achieved much poorer results (Bauer et al, 2002;Chadha et al, 2009;Lanson et al, 2007;Loundon et al, 2003;Young et al, 1995).…”
Section: Candidacy and Selected Aetiologies/pathologies Of Deafnessmentioning
confidence: 99%